Occurrence of patient safety incidents during cancer screening: A cross-sectional investigation of the general public. Issue 43 (28th October 2022) - Mahmudah, Noor Afif; Im, Dasom; Pyo, Jeehee; Ock, Minsu
Abstract : This study aimed to explore the various types and frequency of patient safety incidents (PSIs) during a cancer screening health examination for the general public of Ulsan Metropolitan City, South Korea. Furthermore, the associated elements and responses to PSIs during a cancer screening were examined. The survey, conducted in the five districts of Ulsan, was completed by residents aged 19 years and older who agreed to participate. Descriptive analysis, Chi-square or Fisher exact test, and multivariable logistic regression were performed to analyze the data. A total of 620 participants completed the survey, with 11 (1.8%) individuals who experienced PSIs themselves and 11 (1.8%) by their family members. The highest type of PSIs was those related to procedures. The multivariable logistic regression analysis showed no significant variables associated with experiencing PSIs during cancer screening. However, there was a significant association between the judgment of medical error occurrence and level of patient harm both in experience by family members and total experience of PSIs ( P < .05). There was also a significant difference between with and without an experience of PSIs disclosure ( P < .001). This study comprehensively analyzed the types and extent of PSIs experienced by Korean individuals and their family members in Ulsan. These findings suggest that patient safety issues during cancer screening should not be overlooked. Furthermore, an investigation system to regularly monitor PSIs in cancer screening should be developed and established.